The Effect of Board Size, Audit Committee, Ownership Structure, Independent Commissioners, Leverage, and Firm Size on Financial Distress - Prayitno, Adinda Nurul Oktavia; Mahroji (Journal of Governance, Taxation and Auditing, 2026)
The post-pandemic period represents an economic recovery phase during which many companies face financial pressure due to declining revenues and high debt burdens. This condition is particularly critical in the infrastructure sector, which requires financial stability to sustain long-term operations. This study aims to analyze the effect of corporate governance and ownership structure on financial distress in the infrastructure sector. The data were obtained from companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2024 period using a quantitative approach with purposive sampling. Data analysis was conducted using multiple linear regression. The results indicate that board size and managerial ownership have a significant negative effect on financial distress. These findings support agency theory, which posits that effective internal supervision and managerial ownership can reduce agency conflicts and enhance financial efficiency. Meanwhile, audit committee meeting frequency, independent commissioners, institutional ownership, leverage (DER), and firm size show no significant effect. The study highlights the importance of strengthening corporate governance structures and managerial ownership roles in maintaining financial stability. Future research is recommended to expand the scope and incorporate external factors for a more comprehensive understanding.